Doped polycrystalline silicon thin films deposited on glass from trichlorosilane - Benvenuto, Ariel Gastón (2015)
Atmospheric pressure (AP) thermal CVD is used to deposit thin poly-Si films on glass substrates. Also produced are heterojunction solar cells carrying out the deposition on c-Si wafers. A batch-type hot-wall reactor, employing SiHCl3 as a precursor, H2 as a carrier and reaction gas, BBr3 as a p-type doping agent, and PCl3 as a n-type doping agent, is used. The films obtained are homogeneous and well-adhered to the substrate. Samples are structurally characterized by  scanning electron microscopy (SEM), atomic force microscopy (AFM), reflectance spectroscopy in the UV-vis region, X-ray diffraction (XRD), and Raman spectroscopy (RS). The electrical characterization includes conductivity measurements as a function of temperature, and Hall effect measurements. For the p-doped samples, XRD reveals a strong (220) preferential orientation of the films, while the n-doped samples lack columnar structure or preferential orientation. RS and  UV-reflectance confirm a high crystalline fraction. Dark conductivity measurements as a function of temperature show that the films can be grown intrinsic, p-type or n-type. Activation energies between 0.61 and 0 eV are obtained, with reasonable values for the carrier mobilities. For the solar cells, relatively high values of Voc (507mV) and Jsc (29.6mAcm2) are measured. In conclusion, these results demonstrate the feasibility of directly depositing doped poly-Si thin films on glass and c-Si substrates at intermediate temperatures, with interesting characteristics for photovoltaic applications.